1998
DOI: 10.1038/3276
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 1-independent IL-1β release and inflammation induced by the apoptosis inducer Fas ligand

Abstract: Fas ligand is a well-characterized apoptosis inducer. Here we demonstrate that Fas ligand induces the processing and secretion of interleukin-1beta (IL-1beta) in peritoneal exudate cells. This IL-1beta secretion is independent of IL-1beta converting enzyme (caspase 1), yet it is inhibited by caspase inhibitors, indicating that a caspase(s) in addition to IL-1beta converting enzyme can process IL-1beta. Inoculation of tumor cells expressing Fas ligand into wild-type mice induces a massive neutrophil infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
275
1
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 366 publications
(302 citation statements)
references
References 40 publications
20
275
1
6
Order By: Relevance
“…53 Although caspase-1 has greater specificity for pro-IL-18, other caspases, that is, caspase-3-like proteases, are able to process pro-IL-1b and pro-IL-18 in response to antigenic stimulation or FasL, providing an alternative pathway for cytokine generation. [53][54][55] Consistent with the above reports, we demonstrated the release of IL-18 and IFN-g in response to ConA-induced hepatitis. In addition to inhibiting apoptosis in the liver, mice transduced with CrmA inhibited IFN-g and IL-18 production induced by ConA (Figure 6).…”
Section: Discussionsupporting
confidence: 89%
“…53 Although caspase-1 has greater specificity for pro-IL-18, other caspases, that is, caspase-3-like proteases, are able to process pro-IL-1b and pro-IL-18 in response to antigenic stimulation or FasL, providing an alternative pathway for cytokine generation. [53][54][55] Consistent with the above reports, we demonstrated the release of IL-18 and IFN-g in response to ConA-induced hepatitis. In addition to inhibiting apoptosis in the liver, mice transduced with CrmA inhibited IFN-g and IL-18 production induced by ConA (Figure 6).…”
Section: Discussionsupporting
confidence: 89%
“…Although more studies are needed, the recruitment of neutrophils might be due to the chemotactic effect of FasL. 45,46 In summary, we constructed a bioactive adenoviral vector expressed murine FasL in vitro. In a murine model of OVA-induced asthma, the pulmonary expression of adenoviral vector expressing FasL before the airway challenge could significantly alleviated the development of AHR, reduced the infiltration of eosinophils and lymphocytes, and decreased eosinophil chemoattractant eotaxin, proinflammatory cytokines KC, and TNF-a production, and Th2 cytokines IL-5 and IL-13 production.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism is that CD95L acts on surrounding cells to induce the production of granulocyte chemoattractants. It has been reported that CD95L induces the processing and release of IL-1 g , which may be responsible for the infiltration by neutrophils [41]. CD95L may act on resident macrophages leading to increased production of IL-1 g and macrophage inflammatory proteins [42].…”
Section: Discussionmentioning
confidence: 99%